Small-scale indirect plant responses to insect herbivory could have major impacts on canopy photosynthesis and isoprene emission - Visakorpi, Kristiina (The New phytologist, 2018)
© 2018 The Authors. New Phytologist © 2018 New Phytologist Trust.